ANALISISI PERBEDAAN HASIL BELAJAR SISWA PADA SAAT PEMBELAJARAN TATAP MUKA DAN DARING DI MASA PANDEMI COVID-19 PADA SISWA SDN 11 NANGA PINOH - Agustina, Beti; Mardiana, Mardiana; Rudiansyah, Eko (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
This study aims to determine differences in student learning outcomes during face-to-face and online learning at SD Negeri 11 Nanga Pinoh. The subjects in this study were fourth grade students. This study uses a qualitative method with a case study approach. Data collection techniques in this study used observation and documentation. The procedure in the research includes the preparation stage, the implementation stage, the final stage of the research. The results of the research show that there are differences in results of students’ daily tests during face-to-face and online learning. This is because the learning prosess when online is not optimal, compared to face-to-face learning in face-to-face learning, teachers more easily understand the characteristics of their students than during online learning. Therefore, only 30% of students’ daily test scores during online learning complete the KKM. Whereas during face-to-face learning 70% of students complete the KKM